The Effect Of Two Stay Two Stray Technique Toward Students’ Reading Mastery On Narrative Text - Ali Mardawi; Nur Azmi Rohimajaya (Universitas Mathla'ul Anwar Banten, 2019)
The objective of this research was to investigate whether there was a significant effect of two stay two stray technique toward students’ reading mastery on narrative text at the tenth grade of SMK Mathla’un Nawakartika. The sample of this research was 48 students taken from the tenth grade of SMK Mathla’un Nawakartika. 25 students were from X OTKP as the experimental class and 23 students were from X TKJ as the controlled class.The method used in this study was a quantitative method that designed the experimental.In collecting the data, the researcher conducted test twice to both the classes in which one was as pre-test and another was post-test.And in analyzing the data, the researcher used t-test formula to find out whether there was a significant difference between two variables in this research.The result of statistic calculation obtained that the value of t-observation (to) was 5,60and the degree of freedom (df) was 48. In the table of the significance 5%, the value of (df) = 46 was 1.6735. By comparing the value of to (5,60) with the value of tt (1.6735), it could be seen that the value of to was higher than the value of tt. Then, the alternative hypotheses (Ha) was accepted and the null hypotheses (Ho) was rejected. Based on the result, it could be concluded that there is significant effect of Two Stay Two Stray technique toward students’ reading mastery onnarrative text.